2003
DOI: 10.1046/j.1469-8137.2003.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

Legumes native to longleaf pine savannas exhibit capacity for high N2‐fixation rates and negligible impacts due to timing of fire

Abstract: Summary• N 2 fixation rates of three legume species and the impact of fire regime are reported.• Summer, winter, and no burn treatments were applied. N 2 fixation rates ( 15 N isotope dilution) and C trade-offs with flowering and fine root turnover were examined in response to season of burn.• Tephrosia and Centrosema had uniformly high percentage N dfa across all treatments (74-92% N dfa ), whereas Rhynchosia showed limited N 2 fixation activity (18% and 0%). No evidence for decreased N 2 fixation due to loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Natural sources include the products of microbial mineralization of organic matter and subsequent nitrification and biological dinitrogen fixation, which can contribute 28% of the total N input to pine savannas (Van Breemen et al 2002;Hiers et al 2003;Cohen 2008). In budgets calculated for springsheds in Florida, inorganic fertilizers (containing ammonium) are the largest anthropogenic source of nitrogen, however, the amount of nitrogen that actually reaches the Floridan aquifer from nonpoint sources is difficult to determine.…”
Section: Introductionmentioning
confidence: 99%
“…Natural sources include the products of microbial mineralization of organic matter and subsequent nitrification and biological dinitrogen fixation, which can contribute 28% of the total N input to pine savannas (Van Breemen et al 2002;Hiers et al 2003;Cohen 2008). In budgets calculated for springsheds in Florida, inorganic fertilizers (containing ammonium) are the largest anthropogenic source of nitrogen, however, the amount of nitrogen that actually reaches the Floridan aquifer from nonpoint sources is difficult to determine.…”
Section: Introductionmentioning
confidence: 99%
“…Though longer-term experiments evaluating frequent burning are not common, declines in tree productivity (Boyer, 2000) and N cycling (Wright and Hart, 1997) have been observed. At this longer time scale, N 2 fixation by native herbaceous legumes may play an important role in the N cycle of burned forests by replenishing or even exceeding N lost due to fire Boring, 1992, 1999;Johnson and Curtis, 2001;Caldwell et al, 2002;Hiers et al, 2003). However, the extent of N 2 fixation by legumes in southeastern forests has been examined primarily in certain forest types such as pine plantations or pine savannas Hiers et al, 2003).…”
mentioning
confidence: 99%
“…At this longer time scale, N 2 fixation by native herbaceous legumes may play an important role in the N cycle of burned forests by replenishing or even exceeding N lost due to fire Boring, 1992, 1999;Johnson and Curtis, 2001;Caldwell et al, 2002;Hiers et al, 2003). However, the extent of N 2 fixation by legumes in southeastern forests has been examined primarily in certain forest types such as pine plantations or pine savannas Hiers et al, 2003). Further, interactions between fire effects on legume composition and N inputs via fixation and soil texture have not been addressed over the full range of southeastern forest types currently undergoing prescribed burning.…”
mentioning
confidence: 99%
“…In our study, we observed slightly lower N mineralisation 1 year after fire, which may have benefited Lupinus. Also, N 2 fixation is not always negatively affected by increases in soil N following fire (Hiers et al 2003). Casals et al (2005) found that both seedling and resprouting legume species derived 52-99% of their N from fixation after fire, despite increased amounts of mineral N in burned plots.…”
Section: Discussionmentioning
confidence: 99%